The Axiology of the Traditional Game Jonjang In the Banyumasan Culture Subject - Nur Aisyah, Puji; Mukhroji (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Banyumas has a culture in the form of traditional Jonjang games whose existence is rarely known to today's children. To preserve jonjang in the environment, one of them is to add it to the 4th grade Banyumasan Culture material. This study was made with the aim of reviewing the Axiology of the Jonjang Traditional game in Banyumasan Cultural Subjects. This qualitative research uses document and ethnographic research methods. Data collection was carried out by observing students' activities in practicing the game of jonjang and taking notes from documents obtained from the subject matter, Jonjang songs, and videos related to the discussion in the research. The object in this study is the Jonjang game carried out by students. Researchers analyze data through data collection, data reduction, data presentation, and drawing research conclusions. This study found that the game of jonjang has become an almost extinct game and is not yet known by students today. Jonjang is able to have an impact on students in the process of playing. Jonjang has a fun value, in this case jonjang is done by a group of children. The value of vitality in jonjang can be found in jonjang activities that collaborate between psychic and physical, provide a sportsmanlike attitude, and train the social spirit. The spiritual value of jonjang includes aesthetics when singing songs, then the value of justice and injustice can be seen when changing the installer and guard players